Analisis Ayat Pertama Dan Terakhir Diturunkan Dalam Perspektif Kitab Al-Itqan Fi ‘Ulumil Qur’an Karya Imam As-Suyuti - Wildan Setiawan; Firza Naila Putri (NAAFI: JURNAL ILMIAH MAHASISWA, 2026)
This study aims to examine Imam as-Suyuthi’s perspective in Al-Itqan fī ‘Ulumil Qur’an regarding the first and last verses revealed to the Prophet Muhammad (peace be upon him). Understanding the chronology of revelation plays a crucial role in interpreting the historical, theological, and legal dimensions of Islam. The study employs a qualitative descriptive method through a library research approach, analyzing primary sources from Al-Itqan and relevant secondary references in Qur’anic sciences. The findings reveal that Imam as-Suyuthi discusses various scholarly opinions concerning the first and last revealed verses, both in absolute and thematic contexts. The first revealed verse is generally recognized as QS. Al-‘Alaq [96]:1, while the last remains debated between QS. Al-Baqarah [2]:281 and QS. An-Nasr [110]:1. This study concludes that comprehending the sequence of revelation provides an essential foundation for understanding the evolution of Islamic law, social context, and the completion of the prophetic message.